Influence of Cervical Spine Manipulation on Neck Joint Position Sense error in patients with chronic neck pain. - Miranda, Iã Ferreira; Facchini, Daniel; Manfio, Eliane Fátima (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Cervical joint dysfunction may interfere with the sensorimotor afferent response, interfering with neck neck Joint Position Sense error (JPS). Objective: The aim of this study was to evaluate the influence of Cervical Spine Manipulation (CSM) on neck JPS error in patients with chronic neck pain. Method: 21 patients with chronic neck pain were divided into 2 groups: Spinal Manipulation Group (MG) or Sham Group (SG) who received 4 sessions of CSM and Sham CSM respectively. JPS was assessed in three different time frames: 1) pre-intervention; 2) Right after the first intervention (post-intervention 1); and 3) After a chronic intervention (post-intervention 2). The outcome measured in this study was the head reposition accuracy test with the Revel’s Test. Results: The JPS showed no significant differences between pre- and post-intervention 1 and 2 for any of the assessed groups. Conclusion: We conclude that, for this sample, neither the CSM nor the Sham CSM statistically changed the JPS error for neither groups. We believe that the changes in JPS after CSM were concealed because the ability of other sensory system information to compensate for inadequacies in any other component. Therefore, more studies have to be done with a stronger methodological rigor, clinical prediction rule for spinal manipulation, bigger sample and a blind assessment.